Inherent electrochemistry of layered post-transition metal halides : the unexpected effect of potential cycling of PbI2 - Chua, Chun Kiang (2015)
The development of two-dimensional nanomaterials has expedited the growth of advanced technological applications. PbI2 is a layered inorganic solid with important and unique properties suitable for applications in the detection of electromagnetic radiation. While the optical and electrical properties of layered PbI2 have been generally established, its electrochemistry has remained largely unexplored. In this work, we examine the inherent electrochemistry of PbI2 in relation to its morphological and structural properties. A direct comparison between commercially available and solution-grown PbI2 showed high similarity in properties based on characterizations by X-ray photoelectron spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The respective layered PbI2 materials also exhibited similar inherent electrochemistry. Electrochemical potential cycling of PbI2 in phosphate buffer resulted in the dissolution of iodide ions from PbI2 to form complex lead-phosphate-chloride with the oxygen groups of the phosphate ions while retaining the hexagonal structure. In the case of KCl solution, the formation of PbO2 was observed.